2010
DOI: 10.1103/physreve.82.021504
|View full text |Cite
|
Sign up to set email alerts
|

Binary mixture adsorbed in a slit pore: Field-induced population inversion near the bulk instability

Abstract: The recently proposed method for modulating through an external field the composition of a binary fluid mixture adsorbed in a slit pore is discussed. The population inversion near the bulk (demixing) instability is first analyzed in the case of a symmetric mixture of nonadditive hard spheres, without field. It is next investigated for a mixture comprising dipolar particles subject to an external field. The influence of several factors on the adsorption curves including bulk composition, pore width, field direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…The field effect in this type of system has been studied for one component fluids [10,11] where it was found to gradually increase the fluid density within the pore moderately. A stronger field effect was found by Brunet et al [12,13] who studied mixtures. They observed that if the mixture has a demixing instability and one of the components is dipolar, the coupling to the external field leads to a pore filling transition which allows a sensitive control of the pore composition.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The field effect in this type of system has been studied for one component fluids [10,11] where it was found to gradually increase the fluid density within the pore moderately. A stronger field effect was found by Brunet et al [12,13] who studied mixtures. They observed that if the mixture has a demixing instability and one of the components is dipolar, the coupling to the external field leads to a pore filling transition which allows a sensitive control of the pore composition.…”
Section: Introductionmentioning
confidence: 60%
“…The mechanism we describe should be applicable for a broad class of one-component systems, including molecular fluids and colloidal suspensions. In fact, a nonuniform field should promote phase separation in any dipolar system with an inherent bistable nature [5,6,12,13]. We therefore believe that the study of fluids in nonuniform fields merits further experimental and theoretical attention.…”
Section: Discussionmentioning
confidence: 95%
“…Since colloidal particles are also often polar or polarizable, the combination of geometrical confinement and the action of an external field offers then a unique way to control their behavior in confinement. In recent work, we have shown [5,6] this by Monte Carlo simulation for the simple model of a binary mixture of neutral and dipolar hard-spheres confined between two parallel hard-walls modeling a slit pore. We have shown that the composition of the adsorbed fluid can be controlled in a flexible way by applying an external field in the pore, at fixed thermodynamic state of the bulk fluid.…”
mentioning
confidence: 96%
“…Not having to rely on the subtle combination of specific interactions should also result in a robust method, feasible with simple components. This is why we choose to illustrate the basic mechanisms [5,6] on the simple mixture of neutral and dipolar hard-spheres and perfectly smooth planar walls. The physical situation closest to this model is then the adsorption of colloids, in contrast with molecular adsorption in which specific interactions should be considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation